ANALISIS PERUBAHAN HARGA SAHAM YANG MEMEDIASI FAKTOR-FAKTOR KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Aiji, Annisa Berliana Rantinur; Wiryaningtyas, Dwi Perwitasari; Karnadi, Karnadi (Fakultas Ekonomi dan Bisnis, 2023)
The food and beverage sector is the most important element for survival because it is included in one of the needs that must be met, so that this sector is easy to experience sustainable growth. The studies aimed to anatomize the influence of Return on asset,Debt to equity ratio, and Total asset turnover that influence the enterprise value with share price as an mediation variable at food and beverage enterprise listed at the Indonesia Stock Exchange in 2018-2021. This research is a quantitative research. The population in this research is all enterprise in the food and beverage enterprise listed at the Indonesia Stock Exchange in 2018-2021 into 72 companies . Sampling in this studies used purposive sampling which is obtained samples into 10 companies. The result of the analyze use the smart partial least square (PLS) 3.0 software, show the return on asset has a significant influence on share price, debt to equity ratio has a significant influence on share price, total asset turnover has no significant influence on share price, return on asset has a significant influence on enterprise value, debt to equity ratio has a significant influence on enterprise value, total asset turnover has a significant influence on enterprise value, and stock price has a significant influence on enterprise value. The yield of the indirect effect hypothesis test show that return on assets has a negative and significant influence on enterprise value through share price, debt to equity ratio has a negative and significant influence on enterprise value through share price, and total asset turnover has no significant influence on enterprise value through share price.